Effects of Human Rights Sensitivity of case managers on the working relationships with people suffering from mental illness mediated by empathy - M. Seo; Y.R. Kim (European Psychiatry, 2022)
Introduction It is critical to provide not only mental health services but also welfare services that meet the socioeconomic needs of people suffering from mental illnesses in order for them to recover. Case managers in the public sector who provide socioeconomic support to the low-income class, in particular, play critical roles in early detection of untreated mentally ill people, linking them to the mental health system, and providing various supports for their community integration. Positive working relationships are required to fulfill these roles.